The Information System of Mass Notification in Emergency Situations with an Algorithm of Optimization of Evacuation Plans Based on the Client — Server Architecture - Arutiunian V.E. (Problems of the Regional Energetics, 2019)
The purpose of this article is to develop a modern information system for mass notification. The system must take into account the disadvantages of all existing systems. The aim has been achieved by the development and implementation of the program complex of an algorithm for construction the effective evacuation plans based on the client-server architecture. The complex, in addition to the server and client parts, also uses the Google Maps services. Today, a lot of information systems for the mass notification of the population have been developed. An analytical review of some of them revealed a number of disadvantages related to the efficiency of the systems, the ability to effectively distribute the population to evacuation points or shelters. A feature of the program is an innovative approach for calculation of an effective evacuation plan for each victim, which has not been presented previously. To find an effective path, three parameters are important, i.e., distance; the available spaciousness of the emergency shelter; and speed. Thanks to the algorithm, it is possible to calculate the optimal path for each victim individually, adjusting the distance depending on the speed and fullness of the shelter. The path found will not always be the shortest, but it will be effective for the uniform filling in of the shelters. The effectiveness of the algorithm is presented in the models we programmed in the AnyLogic program. The use of the evacuation model was analyzed using both a short path and the developed algorithm to calculate the most efficient path. The simulated situations show the possibility of saving more people.